Hexagon Fraud Theory Analysis on Financial Statement Fraud - Ratu Persada Pahlevi Pasca Mahardika; Warsito Kawedar (Universitas KH. Abdul Chalim Mojokerto, 2025)
The purpose of this study is to investigate the effect of Hexagon Fraud Theory (financial stability, external pressure, financial targets, nature of the industry, ineffective supervision, external auditor quality, auditor turnover, director turnover, arrogance, and state-owned enterprises) on financial statement fraud. The research sample consisted of 15 construction companies listed on the Indonesia Stock Exchange during the period 2018-2022. This study uses multiple regression analysis to test the research hypothesis. The results show that external pressure, financial targets, the nature of the industry, external auditor quality, auditor turnover, director turnover, and arrogance affect financial statement fraud.